2021
DOI: 10.3390/molecules26154489
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products and Skin Diseases

Abstract: The skin is the largest multifunctional organ in the human body, serving as an excellent barrier against chemical and biological hazards [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Analgesics [28], anticholinesterase [23], and skin photoprotective activities of fireweed extract were also reported [29]. Recently, some studies also showed wound-healing [30] and cosmetic properties of fireweed [31][32][33].…”
Section: Introductionmentioning
confidence: 93%
“…Analgesics [28], anticholinesterase [23], and skin photoprotective activities of fireweed extract were also reported [29]. Recently, some studies also showed wound-healing [30] and cosmetic properties of fireweed [31][32][33].…”
Section: Introductionmentioning
confidence: 93%
“…As a barrier between the internal body and the external environment, the skin may be affected by many conditions such as viral, bacterial, fungal and parasitic infections or UV radiation, that can result in various disorders such as trauma, inflammation, rashes, pigmentation disorders, tumors and even cancer [53]. Nowadays, a wide range of therapeutic methods are used for skin disorders; nevertheless, some of them are limited by adverse reactions, skin barrier or resistance [54].…”
Section: Advanced Technology For Functionalization Of C-pcmentioning
confidence: 99%
“…For example, the excessive use of cleansing cosmetics can disturb the hydrophilic barrier and natural microbiota, cause skin irritations and lead to the atopic skin conditions [54]. This situation is often observed in the inappropriate treatment of acne or self-medication.…”
Section: Advanced Technology For Functionalization Of C-pcmentioning
confidence: 99%
“…Their modes of action are anti-inflammatory, anti-bacterial, anti-pigmentating, and anti-wrinkle formation. The effects are mainly explained by biochemical signaling processes, including antioxidant activities [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%